Tabloid journalism and philosophical discourses surrounding the right to privacy and press freedom - Chama, Brian (International Journal of Media & Cultural Politics, 2015)
Abstract
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9tYWNwLjExLjEuMTA1XzE